The great debate at "Immunotherapy Bridge 2018", Naples, November 29th, 2018. Issue 1 (15th August 2019) - Ascierto, Paolo A.; Butterfield, Lisa H.; Demaria, Sandra; Ferris, Robert L.; Freeman, Gordon J.; Lo, Roger S.; Mantovani, Alberto; Nathan, Paul; Hamid, Omid; Politi, Katerina; Puzanov, Igor
Abstract : As part of the 2018 Immunotherapy Bridge congress (November 28–29, Naples, Italy), the Great Debate session featured counterpoint views from leading experts on four topical clinical issues in immunotherapy today. These were: the relative importance of adaptive versus innate immunity in the anti-cancer immune response; the merits of combination versus sequential immunotherapy regimens in the treatment of cancer; the advantages and disadvantages of murine models of cancer versus humans in order to evaluate immunotherapy; and whether or not mechanisms of resistance to immunotherapy differ between different cancers. Discussion of these important topics are summarised in this report.